The vasorelaxant effect of Adiantum capillus-veneries extract in the vascular activity of goat’s isolated renal artery - Aveen Muhsen Asaad; Ismail Salih Ibraheem (Polytechnic Journal)
The current study represents the first attempt to investigate the effect of Adiantum capillus-veneris extract (ACVE) on goat’s isolated renal artery smooth muscle’s cell. Therefore, this research aims to investigate the possible action of Adiantum capillus-veneris extract (ACVE) (1×10-4–10-9 mg/ml) in the vascular activity of goat isolated renal artery by using the organ bath and PowerLab data acquisition system, and the phytochemical analysis for the ACVE extract was done by using gas chromatography-mass spectrometry (GC/MS). The results of the current study showed that ACVE caused concentration-dependent relaxation of endothelium intact renal artery rings precontracted with a high level of KCl (60 mM) or phenylephrine (PE) (10-5 M), also they are exhibited potent inhibitory effects on PE, and less potent on KCl-induced contractions. Renal artery rings preincubated with potassium (K+) channel blocker (tetraethylammonium, TEA), barium chloride (BaCl2), 4-aminopyridine (4-AP), (indomethacin) and (clotrimazole) showed a significant effect in renal artery smooth muscle relaxation induced by ACVE. While glibenclamide (Glib) and L-NAME did not exhibit any role in the relaxation effect of ACVE. Furthermore, the role of nifedipine L-type calcium channels blocker in the effects of ACVE suggests that a Ca2+ channel blocking mechanism has a relaxant effect in the goat’s renal artery smooth muscles. Renal artery rings preincubated with nifedipine (1×10-5 and 3×10-5 ), and ACVE (1×10-5 and 3×10-5 ), produced a potent inhibitory effect on CaCl2 induced contraction as compared with the control group, and also reduced the maximum contraction. Results of the current study, it can be concluded that ACVE have potent vasorelaxation effects on renal artery rings which are mediated, partly, by the enhancement of PGI2, EET and modulating different K+ channels and Ltype Ca2+ channels activities. Additionally, the results of the current study provide the mechanism of action of some constituents of the medicinal plant Adiantum capillus-veneris which can be exploited to develop more specific drugs to be used for the treatment of various vascular diseases based on phytochemical analysis of the extract.